PROFIL METABOLIK PENGGUNA ROKOK ELEKTRIK MELALUI PEMERIKSAAN GLUKOSA DARAH PUASA, LIPID, DAN ASAM URAT - Mega Pratiwi Irawan; Safri Mawaddah; Rara Septianna; Nurainil Sapitri; Mutiara Kasih5; Intan Yuliani; Widia Kurnia Sari; Rosa Devitria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract : The use of e-cigarettes is increasing and is often considered safer than conventional cigarettes. However, chemical compounds such as nicotine, glycerin, and carbonyl compounds in e-cigarettes still have the potential to affect health, especially the cardiovascular and metabolic systems. This study aims to determine the levels of fasting blood glucose, triglycerides, total cholesterol, and uric acid in e-cigarette users in Kecamatan Payung Sekaki. This is a descriptive study with a cross-sectional approach involving 22 male respondents aged 20–35 years who met the inclusion and exclusion criteria. Laboratory examinations were conducted using the GOD-PAP, GPO-PAP, CHOD-PAP, and Uricase-PAP methods. The results showed that 36.36% of respondents had above-normal fasting blood glucose levels, 22.73% had high triglyceride levels, 54.55% had abnormal total cholesterol levels, and 50% had abnormal uric acid levels. In addition, a trend towards an increase in all parameters was found in respondents who had used e-cigarettes for more than 3 years. Based on the research results, it can be concluded that e-cigarette users show a tendency toward abnormalities in several metabolic parameters associated with the risk of cardiovascular disease, especially with long-term use.Keywords: e-cigarettes, fasting blood glucose, triglycerides, total cholesterol, uric acid